Left-right asymmetry in embryonic development: how epigenetic, biophysical forces and gene activity interplay to determine a major embryonic axis - Levin, Michael (Henry Stewart Talks, 2011)
Types of symmetry in animal bodyplans, Left-right asymmetry definition, Human laterality, facts about normal human asymmetry, Ways asymmetry can go wrong, Clinical applications of left-right asymmetry, Left-right pathway, Asymmetric gene expression, Loss-of-function pharmacological screen, Ion transporters in left-right patterning, Novel localization mechanisms, Molecular loss-of-function experiments, Gain-of-function experiments, Expression and function of the ion flux system, Serotonin: a neurotransmitter with many roles, Serotonin and asymmetry, Phases during left-right patterning, The relationship between physiological signals and the ciliary model of LR asymmetry, Is nodal flow required for consistent asymmetry?, 3 fundamental models of LR asymmetry